2018
DOI: 10.1080/01441647.2018.1441923
|View full text |Cite
|
Sign up to set email alerts
|

From hierarchy to networking: the evolution of the “twenty-first-century Maritime Silk Road” container shipping system

Abstract: Container shipping gives a rise of international trade since the 1960s. Based on navigation data start from the mid-1990s to 2016, this paper empirically analyses the spatial pattern of China's international maritime linkages along the "twenty-first-century Maritime Silk Road". We interpret such evolutionary dynamics in terms of growth, hierarchical diffusion and networking phases. Networking is a new stage of the evolution of the port system, which is approached based on the graph theory, complex network meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 43 publications
0
25
0
1
Order By: Relevance
“…This paper establishes the lag relationship between ship frequency and oil price by using the ARDL model and compares the differences between different regions along the MSR affected by the oil price slump and changes of tanker cargo flow distribution. The following conclusions are drawn: (1) There is a significant negative correlation between tanker shipping frequency and oil price in the same period, that is to say, the shipping frequency will increase correspondingly when oil price slumps. The correlation between maritime export cargo flow situation and oil price is stronger than that of import cargo flow situation.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This paper establishes the lag relationship between ship frequency and oil price by using the ARDL model and compares the differences between different regions along the MSR affected by the oil price slump and changes of tanker cargo flow distribution. The following conclusions are drawn: (1) There is a significant negative correlation between tanker shipping frequency and oil price in the same period, that is to say, the shipping frequency will increase correspondingly when oil price slumps. The correlation between maritime export cargo flow situation and oil price is stronger than that of import cargo flow situation.…”
Section: Discussionmentioning
confidence: 84%
“…Assuming that the original data i x and i y have been arranged in descending order and that ' (1) In the case of the same rank before and after ordering, the linear correlation coefficients of Pearson between ranks should be calculated according to Equation (2), where x and y is the mean of the sample variables.…”
Section: Spearman Rank Correlation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These new vessels can carry 18,000 TEUs with low operational cost and efficient service. This can help Maersk to establish itself in those fast growing markets where speed and timeliness factors are critical (Campo‐Flores & McWhirter, ; Heins, ; Hirata, ; Wang, Zhu, Ducruet, Bunel, & Lau, ).…”
Section: Future Developments and Growth Prospectsmentioning
confidence: 99%
“…The results have indicated that the spatial expansion of the China's international shipping network has generally been taking place also driven by inclusion of more foreign seaports into the "Maritime Silk Road" network configuration. The role of the large seaports such as Hong Kong and Shanghai in such growing network has also changed including more diversification and consequent managerial implications (Wang et al 2018). As well, the specific research has been dealing with the research of liner container shipping networks over the period 1967-2013.…”
Section: Modelling the Indicators Of Performances Of A Trunk Line/roumentioning
confidence: 99%